2020
DOI: 10.3389/fneur.2019.01336
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural and Functional Imaging Findings in Medication-Overuse Headache

Abstract: This chapter overviews research neuroimaging findings of patients with medication-overuse headache (MOH). Results indicate; (i) correlations between neuropathology and medication-overuse; (ii) changes in brain morphology and cortical function; and (iii) brain recovery subsequent to withdrawal of medication that was overused. Results of this narrative review indicate exacerbated brain structural and functional changes in regions of the pain-matrix and in regions of the mesocortical-limbic circuit in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Taken together, these results reflect functional and morphological reorganization of subcortical and cortical structures due to central sensitization and dysfunctioning central pain control mechanisms in CM-MOH patients (32,40,41).…”
Section: Discussionmentioning
confidence: 57%
“…Taken together, these results reflect functional and morphological reorganization of subcortical and cortical structures due to central sensitization and dysfunctioning central pain control mechanisms in CM-MOH patients (32,40,41).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, after medication withdrawal, other regional metabolic changes were found to normalize in this study, with the exception of continued hypometabolism in the orbitofrontal region (Fumal et al, 2006 ), which might be related to the fact that the orbitofrontal cortex plays a role in addictive disorders. Moreover, the results of structural imaging studies have revealed abnormalities, including lower orbitofrontal cortex volume and thickness (Chong, 2019 ). Therefore, the decreased NVC in ORBsup.L observed in the current study is consistent with the abovementioned previous functional and structural studies, which could be used to explain MOH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of the functional characteristics of the brain in CM − MOH during the interictal phase, using static functional connectivity and static and dynamic functional network connectivity analyses, found that the abnormal connectivity pattern between sensory and cognitive brain networks and altered connectivity were concentrated in the executive control network of the CM patients [50]. Compared to patients with a migraine, patients with MOH exhibit exacerbated changes in brain structure and function in regions of the pain matrix and areas of the mesocortical-limbic circuit [51].…”
Section: Discussionmentioning
confidence: 99%